The Effect Of Third Party Funds, Loan To Deposit Ratio, Non Performing Loans And Return On Assets On The Amount Of Credit Distribution - Pela Sopilah; Apiatno; Lisna Lisnawati (LPPM Universitas Sebelas April, 2020)
Banks are financial institutions that work as intermediaries by receiving money deposits from the public and then flowing them back in the form of credit. The background of this research is that the distribution of credit provided by banks is not optimal, so this research was conducted to obtain empirical evidence about the effect of Third Party Funds, Loan to Deposit Ratio, Non Performing Loans and Return On Assets on Total Credit Distribution. This research was conducted at PT. Bank Rakyat Indonesia (Persero) Tbk period 2015-2019. The method of data collection in this research is by downloading the financial statements on the website of PT. Bank Rakyat Indonesia. The data analysis method used in this study used descriptive statistical analysis, normality test, and multiple linear regression analysis. The tests that have been carried out in this study have shown that Third Party Funds, Loan to Deposit Ratio, Non Performing Loans have a significant positive effect on the amount of credit disbursement. Meanwhile, Return on Assets has a significant negative effect on the amount of lending